PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Panca Wahyuningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
The objective of this research is to investigate the impact of institutional ownership structure and corporate governance to earning management. The measure of institutional ownership was defined on percent of owner stocks by investor and corporate governance is measured in four variables ( independen comisaries proporsional, size of comisaries, audit commite and size of corporate). The analize methode is linear regresion. Tis reasearch used empirical data in Indonesia stock exchange with 20 company of bank periode 2004 – 2006 .The result of this research indicate all variables: institusional ownership, independent commisaries bord , size of commisaries, audit commitee and size of corporate are not significant to earning management.